The Role of Mitochondria for the Regulation of Cardiac Alternans - Florea, Stela M.; Blatter, Lothar A. (Frontiers in Physiology, 2010)
Electromechanical and Ca alternans is a beat-to-beat alternation of action potential duration, contraction strength and Ca transient amplitude observed in cardiac myocytes at regular stimulation frequency. Ca alternans is a multifactorial process that is causally linked to cardiac arrhythmias. At the cellular level, conditions that increase fractional release from the sarcoplasmic reticulum or reduce diastolic Ca sequestration favor the occurrence of alternans. Mitochondria play a significant role in cardiac excitation-contraction coupling and Ca signaling by providing the energy for contraction and ATP-dependent processes and possibly by serving as Ca buffering organelles. Here we tested the hypothesis that impairment of mitochondrial function generates conditions that favor the occurrence of Ca alternans. Alternans were elicited by electrical pacing (>1 Hz) in single cat atrial myocytes and intracellular Ca ([Ca]i) was measured with the fluorescent Ca indicator Indo-1. The degree of alternans was quantified as the alternans ratio (AR=1-S/L, where S/L is the ratio of the small to the large amplitude of a pair of alternating Ca transients). Dissipation of mitochondrial membrane potential (with FCCP) as well as inhibition of mitochondrial F1/F0-ATP synthase (oligomycin), electrontransport chain (rotenone, antimycin, CN-), Ca-dependent dehydrogenases and mitochondrial Ca uptake or extrusion, all enhanced AR and lowered the threshold for the occurrence of Ca alternans. The data indicate that impairment of mitochondrial function adversely affects cardiac Ca cycling leading to proarrhythmic Ca alternans.